Promoting Maqashid al-Shari'ah and Achieving Sustainable Economic Development: the Potential of Proposed Two Tier Mudarabah Business Model on Cash Waqf - Abu Umar Faruq Ahmad; Mohammad Ashraful Mobin (Sharia and Law Faculty, 2017)
Islamic microfinance provides an alternative model for a significant number of underprivileged people who are not served by conventional microfinance. In order to give access to sustainable services to a greater extent, the Islamic microfinance is in paramount need of the adoption of innovative business models and sound practices into the industry. To this end, the research seeks to propose two tier mudarabah model based on cash waqf as an alternative to Islamic microfinance institutions. The objectives of the study are: to a) help develop and implement an appropriate business model; b) safeguard the maqasid al-Shari`ah so as to promote the well-being of the people through establishing justice and eliminating hardship; and 2) help make a reform in the present institutional framework for Islamic microfinance and waqf institutions. The study finds that cash waqf based microfinance institutions can play an important role inter alia in financial inclusion and developing socio-economic conditions of the poor and underprivileged people in society.